Learner’s Autonomy In English As A Foreign Language Teaching And Learning: A Case Study At A State University in Indonesia - Rahma Sakina; Eva Meidi Kulsum; Bachrudin Musthafa (Biormatika : Jurnal ilmiah fakultas keguruan dan ilmu pendidikan, 2022)
This article presents the outcome of a case study research which is particularly aimed at investigating dimensions of learner autonomy in EFL teaching-learning particularly in an English education program and situations under which learners learn autonomously. To collect the data, a questionnaire adapted from Murase (2009) was distributed to fourty first-year undergraduate students of a university in Bandung and interview was addressed to nine undergraduate learners. The findings showed that all dimensions of learner autonomy are found and each dimension is reflected in various degrees. The degree of technical and political dimensions of learner autonomy is in respect not as satisfactory as expected. However, the degree of learner autonomy in the psychological and socio-cultural dimension is high enough. There are four major aspects related to situations under which learners learn autonomously, including the subject matter, the lecturer, the time, and the challenging task. It is recommended for further research to investigate learner autonomy in a more specific context of class, for example learner autonomy in a speaking class, in order to get more in-depth data.